'Pseudomonas saudiphocaensis' sp. nov., a new bacterial species isolated from currency notes collected during the Hajj pilgrimage in 2012 at Makkah, Saudi Arabia. (January 2017) - Azhar, E.I.; Papadioti, A.; Bibi, F.; Ashshi, A.M.; Raoult, D.; Angelakis, E.
Abstract: We report here the main characteristics of 'Pseudomonas saudiphocaensis' strain 20_BN T (CSUR P1224), a new species of the Pseudomonas genus that was isolated from currency notes collected during the Hajj pilgrimage in 2012 at Makkah, Saudi Arabia.